2016
DOI: 10.1186/s12912-016-0142-x
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent validity of self-rating scale of self-directed learning and self-directed learning instrument among Italian nursing students

Abstract: BackgroundSelf-Directed Learning develops when students take the initiative for their learning, recognising needs, formulating goals, identifying resources, implementing appropriate strategies and evaluating learning outcomes. This should be seen as a collaborative process between the nurse educator and the learner. At the international level, various instruments have been used to measure Self-Directed Learning abilities (SDL), both in original and in culturally-adapted versions. However, few instruments have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 30 publications
1
38
0
2
Order By: Relevance
“…With regards to the second aim of the study, participants reported an average SRSSDL O score of 54.27 ± 6.69 out of 65, indicating high SDL abilities. In all items, scores were on average >3 (from 3.61 to 4.65) similarly to those reported by healthcare students and professionals (from 3.53 to 4.01) in previous studies (Cadorin, Cheng, et al, ; Cadorin et al, ). According to Williamson (Williamson, ) scores <3 should be considered areas in which the learner needs to improve his/her SDL abilities.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…With regards to the second aim of the study, participants reported an average SRSSDL O score of 54.27 ± 6.69 out of 65, indicating high SDL abilities. In all items, scores were on average >3 (from 3.61 to 4.65) similarly to those reported by healthcare students and professionals (from 3.53 to 4.01) in previous studies (Cadorin, Cheng, et al, ; Cadorin et al, ). According to Williamson (Williamson, ) scores <3 should be considered areas in which the learner needs to improve his/her SDL abilities.…”
Section: Discussionsupporting
confidence: 85%
“… In this phase the items were numbered according to their original order as reported in Self‐Rating Scale of Self‐Directed Learning (SRSSDL) (Cadorin et al, , ; Cadorin, Cheng, et al, ) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations